Comprehensive Germline Genomic Profiling of Patients with Ovarian Cancer: A Cross-Sectional Study - Pramanik, Raja; Upadhyay, Avinash; Khurana, Sachin; Kumar, Lalit; Malik, Prabhat S.; Kumar, Sunesh; Ray, M. D.; Deo, S. V. S.; Gupta, Ritu; Thakral, Deepshi; Thulkar, Sanjay; Ramprasad, V. L. (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Ovarian cancer is the third most common cancer among Indian women. The data on the hereditary predisposition of these cancers and the clinical outcomes of those with pathogenic mutations is meager in India.Objective The aim of the current study was to analyze the germline-genetic profile, clinicopathological characteristics, and outcomes of patients with ovarian cancer who were referred for genetic counseling at our Institute.Materials and Methods It was a cross-sectional observational study. Patients with histological diagnosis of carcinoma ovary at our institute who were referred for genetic counseling from July 2017 to June 2020 were included in the study. All patients underwent pretest counseling. Most patients underwent multigene panel testing with reflex multiplication ligation-dependent probe amplification for large genomic rearrangements, while some received testing for BRCA1 and BRCA2 only. The variants were classified as pathogenic or benign based on American College of Medical Genetics (ACMG) guidelines. Data regarding the demographic profile, clinical characteristics, histopathological findings, family history, treatment received, and outcomes were extracted from the medical record system files.Results One hundred and one patients were referred to the genetic clinic and underwent genetic counseling. All patients were advised for genetic testing; however, only 72 (71%) underwent testing. A multigene panel testing was done in 51 (70%) patients, and only BRCA1 and BRCA2 genes were tested in 21 (30%). Among the 72 patients who underwent a genetic test, the median age was 47 years (range, 28–82). The most common histopathology was serous (90%), while 85% were diagnosed having stage 3 and 4 ovarian cancer. A pathogenic/likely pathogenic (P/LP) BRCA or non-BRCA mutation was detected in 32 (44%) patients. Six patients (8%) had a variant of unknown significance (VUS). Among P/LP mutations, 85% were in the BRCA gene (75% in BRCA1 and 10% in BRCA2), while 15% were in non-BRCA gene mutations (RAD51, PALB2, MER11, HMMR). Disease-free survival and overall survival were not different in mutation-positive and mutation-negative cohorts.Conclusions We report 44% P/LP mutations in this selected cohort of patients with carcinoma ovaries. BRCA mutations constituted 85% of all the mutations, while 15% of mutations were in non-BRCA genes.
Keywords: germline; ovarian cancer; BRCA